Knowledge and attitude of insecticide-treated net use in malaria prevention and its associated factors among pregnant women in Umuahia North, Nigeria - Onyinyechi, Opara Monica (2017)
Background: Malaria is an infectious disease which infects millions of people worldwide every year. The disease is a global health problem, which affect mainly young children especially those less than five years of age and pregnant women. Objective:The aim is to determine the level of knowledge and attitude of insecticide treated nets (ITNs) use in malaria prevention and its associated factors among pregnant women in Umuahia North, Nigeria. Methodology: A cross-sectional study was carried out using simple random sampling to select two hospitals among 10 hospitals; afterwards, simple random sampling with proportionate to size was employed to select the number of participants from each of the hospitals using guided self-administered questionnaire distributed to the pregnant women who met the inclusion criteria and came for antenatal visit. Data was collected using a pre-tested and validated questionnaire consisting of 5 sections involving the socio-demographic characteristics, knowledge, attitude, perceived barriers and maternal factors. The knowledge was measured using “Yes”, “No” or I don’t knowoptions; The attitude was measured on a 5-point likert scale “strongly disagree” [0], “disagree” [1], “unsure” [2], “agree” [3], “strongly agree” [4]; perceived barriers was measured on a 5-point likert scale “strongly disagree” [0], “disagree” [1], “unsure” [2], “agree” [3], “strongly agree” [4]; past history of malaria related complication was measured using “Yes” or “No” options; while the questions on maternal factors were also measured. Three level of analyses were conducted which were descriptive analysis, chi-square and logistic regression. The significance level was set at 0.05. Results: A total of 426 respondents were involved in the study with 97.3% responserate. The overall mean knowledge score of the respondents was 6.85 (± 0.503), with 90.7% of having high knowledge on insecticide treated nets (ITNs) in malaria prevention. However, 51.1% (mean = 40.09, SD ± 5.5237) of the respondents held positive attitude. Majority of the respondents among the age group of 25-34years were 341 (77.5), 414 (94.1) were Igbos, 401 (91.1) were married. Majority of the respondents 339 (77.0) were currently living in Urban, 342 (77.7) held tertiary education, Most of the respondents earned 71,000 and above, and more than half 294 (66.8) of the respondents had no past history of malaria related complication. There were significant association between knowledge regarding the use of insecticide treated nets and ethnicity (P= 0.001), monthly income (X2=11.957, P= 0.008), parity (X2=8.487, P= 0.014), and also perceived barriers (X2=5.812, P= 0.016). However, there was significant independent predictors of knowledge on insecticide treated nets (ITNs) use and ethnicity (AOR=4.891, p = 0.024, 95% CI=1.231-19.429), in which those with higher odds of having high knowledge. Monthly income (AOR=0.358, p = 0.015, 95% CI=0.157-0.820), and also level of education (AOR=3.715, p = 0.019, 95% CI=1.244-11.094). There were significant association between attitude towards the use of insecticide treated nets and age (X2=44.801, P= 0.001), marital status (P= 0.008), monthly income (X2=139.417, P= 0.001), educational status (X2=23.544, P= 0.001), past history of malaria related pregnancy complication (X2=70.113, P= 0.001), stages of pregnancy (X2=57.244, P= 0.001), gravidity (X2=38.881, P= 0.001), parity (X2=25.116, P= 0.001) and perceived barrier (X2=144.423, P= 0.001). Furthermore, there was significant independent predictors of attitude towards the use of insecticide treated nets (ITNs) and monthly income (AOR= 0.257, p = 0.001, 95% CI=0.124-0.531), in which those with lower odds of having positive attitude. Past history of malaria related complicated pregnancy (AOR=1.858, p = 0.043, 95% CI=1.019-3.386), and Perceived barriers (AOR=1.435, p = 0.001, 95% CI=1.284-1.605). Conclusion: This study has identified that there is high level of knowledge, negative attitude among pregnant women in Umuahia North LGA, Abia State. However, predictors of knowledge and attitude were also determined.